2022
DOI: 10.4103/ijo.ijo_2107_21
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Ahmed glaucoma valve and transscleral cyclophotocoagulation in neovascular glaucoma

Abstract: Purpose: To determine the outcomes of Ahmed glaucoma valve (AGV) and transscleral diode cyclophotocoagulation (CPC) in neovascular glaucoma (NVG). Methods: This was a single-center retrospective comparative case series involving chart review of consecutive patients who underwent AGV or CPC for treatment of NVG and had ≥6 months of follow-up. Surgical failure at 6 months, defined as an IOP of >21 or <6 mm Hg with hypotony maculopathy after 1 month, progression to no ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…Several risk factors for failure after AGVI including age, ( 33 ) baseline IOP, ( 34 ) presence of NVI before surgery, ( 22 ) the presence of SO, ( 28 ) no PRP before AGVI, ( 9 ) and bleb encapsulation ( 30 ) have been reported in NVG eyes. In our series, the eyes filled with SO were excluded and PRP was performed before AGVI in all enrolled eyes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several risk factors for failure after AGVI including age, ( 33 ) baseline IOP, ( 34 ) presence of NVI before surgery, ( 22 ) the presence of SO, ( 28 ) no PRP before AGVI, ( 9 ) and bleb encapsulation ( 30 ) have been reported in NVG eyes. In our series, the eyes filled with SO were excluded and PRP was performed before AGVI in all enrolled eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Univariate analysis showed that preoperative high IOP and the history of intravitreal anti-VEGF treatment were related with surgical failure; however, in multivariate analysis, the only factor associating with failure was anti-VEGF therapy before AGVI. The results about the effect of previous intravitreal anti-VEGF injection on the outcomes of glaucoma surgery for the treatment of NVG are controversial (9,(34)(35)(36)(37). It has been reported that pre-operative intravitreal anti-VEGF injection in NVG patients could increase the success rate of AGVI in some studies, (35,36) while others have not been demonstrated any difference between the groups between eyes with and without anti-VEGF pretreatment (9,34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that in published studies of predictors of surgical failure or success, baseline IOP, visual field mean deviation, and glaucoma staging have not been found to be predictors of success in primary Xen implantation [ 25 ], but are significant in primary tube shunt surgery [ 26 , 27 ]. In CPC, baseline IOP was found to be a significant predictor of failure in neovascular glaucoma [ 28 ]. It should be noted that these studies have variable definitions of success and failure, some of which include a maximum allowed IOP and others which only define failure as reoperation.…”
Section: Discussionmentioning
confidence: 99%
“…Allerdings haben die Autoren in der zitierten Studie relativ hohe Energieeinstellungen gewählt. In einer rezenten Studie aus dem Jahr 2022 trat eine Hypotonie nach Zyklophotokoagulation nur bei 1 von 51 Patienten auf [50]. Entsprechend ist bei der Anzahl der Applikationen bzw.…”
Section: Caveunclassified